2002
DOI: 10.1067/mhn.2002.126723
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Brainstem Implantation: The University of Verona Experience

Abstract: We believe that the RS approach is the route of choice for patients who are candidates for ABI due to the easy and clear access to the cochlear nucleus area. This route avoids some of the drawbacks of the translabyrinthine approach, such as mastoidectomy, labyrinthectomy, sealing of the cavity and posterior fossa with abdominal fat, and contamination from the middle ear. For this reason, it is the route of choice in children with cochlear nerve aplasia or severe cochlear malformation and in adults with complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 31 publications
0
52
0
6
Order By: Relevance
“…The hearing and speech evaluation of the implantees has been performed in different ways among authors. Colletti et al [1,6,9,22] and Kalamarides et al [15] tested hearing using the following tests: (1) recognition of environmental sound or sound detection test; (2) closed-set vowel confusion test; (3) closed-set consonant confusion test; (4) closed-set word recognition in the vision-only mode (lip-reading), sound-only mode, and "sound plus-vision mode"; (5) open-set sentence recognition in the vision-only mode, sound-only mode, and sound-plus-vision mode; and (6) speech-tracking test [9,18] . Goffi-Gomez et al [13] and Eisenberg et al [24] used the "Infant Toddler Meaningful Auditory Integration Scale" (IT-MAIS) to evaluate hearing capacity and the "Meaningful Use of Speech Scale" (MUSS) to evaluate speech performance.…”
Section: Commentmentioning
confidence: 99%
See 4 more Smart Citations
“…The hearing and speech evaluation of the implantees has been performed in different ways among authors. Colletti et al [1,6,9,22] and Kalamarides et al [15] tested hearing using the following tests: (1) recognition of environmental sound or sound detection test; (2) closed-set vowel confusion test; (3) closed-set consonant confusion test; (4) closed-set word recognition in the vision-only mode (lip-reading), sound-only mode, and "sound plus-vision mode"; (5) open-set sentence recognition in the vision-only mode, sound-only mode, and sound-plus-vision mode; and (6) speech-tracking test [9,18] . Goffi-Gomez et al [13] and Eisenberg et al [24] used the "Infant Toddler Meaningful Auditory Integration Scale" (IT-MAIS) to evaluate hearing capacity and the "Meaningful Use of Speech Scale" (MUSS) to evaluate speech performance.…”
Section: Commentmentioning
confidence: 99%
“…The translabyrinthine approach is the only one allowed by the FDA, [15,22] as it is considered by some authors as the most straightforward way to the foramen of Luschka, but experimental evidence suggests the necessity for more manipulation in order to observe the lateral recess, increasing the risks [22] . Bento et al [19] showed the feasibility of exposing of the jugular bulb without complications when using the retrolabyrinthine approach.…”
Section: Commentmentioning
confidence: 99%
See 3 more Smart Citations